2022
DOI: 10.1186/s13321-022-00666-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting chemical structure using reinforcement learning with a stack-augmented conditional variational autoencoder

Abstract: In this paper, a reinforcement learning model is proposed that can maximize the predicted binding affinity between a generated molecule and target proteins. The model used to generate molecules in the proposed model was the Stacked Conditional Variation AutoEncoder (Stack-CVAE), which acts as an agent in reinforcement learning so that the resulting chemical formulas have the desired chemical properties and show high binding affinity with specific target proteins. We generated 1000 chemical formulas using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For better generalization of moBRCA-net, we adopted a data augmentation based on the deep generative model to enlarge the training dataset size. Several recent papers have shown that conditional variational autoencoder (CVAE)-based data generation for certain minority classes in the imbalanced dataset improved the classification performance in various domain tasks such as respiratory disease classification [ 41 ], temporal pattern prediction based on electronic health records [ 42 ], and prediction of chemical structure based on the chemical properties [ 43 ]. We constructed a conditional variational autoencoder (CVAE) composed of two-layered encoder and decoder, which estimates the conditional distribution with latent variables and data, and generates samples for specified breast cancer subtype.…”
Section: Resultsmentioning
confidence: 99%
“…For better generalization of moBRCA-net, we adopted a data augmentation based on the deep generative model to enlarge the training dataset size. Several recent papers have shown that conditional variational autoencoder (CVAE)-based data generation for certain minority classes in the imbalanced dataset improved the classification performance in various domain tasks such as respiratory disease classification [ 41 ], temporal pattern prediction based on electronic health records [ 42 ], and prediction of chemical structure based on the chemical properties [ 43 ]. We constructed a conditional variational autoencoder (CVAE) composed of two-layered encoder and decoder, which estimates the conditional distribution with latent variables and data, and generates samples for specified breast cancer subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have tackled the RL problem by defining an action space, a state, a policy, and an environment. The action space composed of symbol sets that represent molecular structures, a state space made up of symbol substrings, a policy for predicting the next appropriate symbol (action) to append to the current substring (state) up to a certain length, and an environment that evaluates the completed string, providing rewards based on its properties [10,11,16,18]. Policies employ deep neural network models, such as RNNs, to deal with string-based molecular structures.…”
Section: Reinforcement Learning For Molecular Generationmentioning
confidence: 99%
“…To address these challenges, many studies have used the simplified molecular-input line-entry system (SMILES), self-referencing embedded strings (SELFIES) [7,8], and graph-based representation methods [9] in training deep molecular generative models. Researchers have exploited various deep generative models, including recurrent neural networks (RNNs) [10,11], transformers [12], and graph neural networks (GNNs) [9], to efficiently handle those string-based or graph-based molecular data [13,14]. Furthermore, Bayesian optimization [9,15] and reinforcement learning (RL) techniques [10,16,17] have been exploited for deep molecular generative models to create molecules with desired chemical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations